Rest–activity rhythm associated with depressive symptom severity and attention among patients with major depressive disorder: a 12-month follow-up study - Yang, Hang-Ju; Cheng, Wan-Ju; Hsiao, Mi-Chun; Huang, Sheng-Che; Kubo, Tomohide; Hang, Liang-Wen; Lee, Wei-Sheng (Frontiers in Psychiatry, 2023)
Introduction: Patients with depressive disorder demonstrate rest-activity rhythm disturbances and cognitive function impairment. This study examined the association of individual rest-activity rhythm changes over time with mood symptoms and attention.We recruited 15 adult outpatients with a diagnosis of major depressive disorder from a single medical center and observed them for 12 months. Weekly rest-activity parameters, including rhythm characteristics generated from nonparametric circadian rhythm analysis, were retrieved from actigraphy data.Attention was evaluated weekly with a smartphone-based psychomotor vigilance test upon awakening. Depressive symptom severity was evaluated using the Beck Depression Inventory (BDI) fortnightly. The association of rest-activity parameters with BDI score and attention was examined using generalized linear mixed regression.A fixed-effects analysis was used to examine the association between rest-activity parameters and depressive episodes.Results: An advanced bedtime and most active continuous 10 h starting time were associated with depressive symptom severity but also associated with higher vigilance test performance. A longer sleep duration, mainly due to an earlier bedtime, was associated with depressive symptom severity. Compared to remission, sleep duration was 27.8 minutes longer during depressive episodes, and bed time was 24 minutes earlier. A shorter sleep duration and increased activity during sleep were associated with poorer attention. Discussion: Rest-activity rhythms change with mood symptoms among patients with depressive disorder. The circadian rhythms of rest-activity among patients with depressive disorder should be distinguished during various mood states in future studies.